Monitoring of Cerebral Blood Flow Autoregulation after Cardiac Arrest - Rok Petrovčič; Martin Rakusa; Andrej Markota (Medicina)
Background: Cardiac arrest remains one of the leading causes of death. After successful resuscitation of patients in cardiac arrest, post-cardiac arrest syndrome develops, part of it being an impaired cerebral blood flow autoregulation. Monitoring cerebral blood flow autoregulation after cardiac arrest is important for optimizing patient care and prognosticating patients’ survival, yet remains a challenge. There are still gaps in clinical implications and everyday use. In this article, we present a systematic review of studies with different methods of monitoring cerebral blood flow autoregulation after non-traumatic cardiac arrest. Methods: A comprehensive literature search was performed from 1 June 2024 to 27 June 2024 by using multiple databases: PubMed, Web of Science, and the Cochrane Central Register of Controlled Trials. Inclusion criteria were studies with an included description of the measurement of cerebral blood flow autoregulation in adult patients after non-traumatic cardiac arrest. Results: A total of 16 studies met inclusion criteria. Our data show that the most used methods in the reviewed studies were near-infrared spectroscopy and transcranial Doppler. The most used mathematical methods for calculating cerebral autoregulation were cerebral oximetry index, tissue oxygenation reactivity index, and mean flow index. Conclusions: The use of various monitoring and mathematical methods for calculating cerebral blood flow autoregulation poses a challenge for standardization, validation, and daily use in clinical practice. In the future studies, focus should be considered on clinical validation and transitioning autoregulation monitoring techniques to everyday clinical practice, which could improve the survival outcomes of patients after cardiac arrest.